THE PLANNING MODEL OF APPLICATION TO INCREASE THE PRODUCTION ON THE FURNITURE BUSINESS - Irma Nurmala Dewi; Khaeruman Khaeruman (Yayasan Education and Social Center, 2021)
This research is based on the importance of planning in the world of business, especially in terms of production which of course will not be separated from a considerable expense. With planning, the company can figure out the amount to be produced, whether it is too large or too low. If in production there are deviations from the predetermined plan, it will be costly to the company concerned and the use of high costs in the production stage will disserve to the company. This research is qualitative research that aims to find out and explain the planning carried out in the Furniture Business in 2021. The purpose of this study is to describe how the implementation of Furniture Business planning,increase production. The result of this research is that the Furniture Business in the production of goods has planned as before, it can be proven in 2021 in the sales budget for One Package of Living Room Chairs which will be carried out in 2021, with a sales plan of 47 units and a sales budget of Rp. 94.000.000. As for the wardrobe sales budget which will be carried out in 2021, with a sales plan of 43 units and a sales budget of Rp.38.700.000, based on estimation results using three production approaches, that emphasize the stability of production, prioritizing inventory stability, and the combination of inventory and production levels fluctuating at certain limits. Furniture business for the final result is still an optimum balance between the level of production and the supply of inventory levels